2017
DOI: 10.3892/ol.2017.6276
|View full text |Cite
|
Sign up to set email alerts
|

Association between the BRAF V600E mutation and ultrasound features of the thyroid in thyroid papillary carcinoma

Abstract: The aim of the present study was to investigate the association between the BRAF V600E mutation and ultrasound features of the thyroid in papillary thyroid carcinoma (PTC). Fresh thyroid carcinoma tissue and paracarcinoma tissue were obtained from 34 patients undergoing surgery for PTC. The BRAF V600E mutation was detected by PCR amplification and direct DNA sequencing. The thyroid ultrasound results were compared between patients with and without the BRAF V600E mutation. Eighteen out of 34 cases were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Luo et al (25) reported that the BRAFV600E mutation was associated with the features of the nodules on elastography, but not with the features on 2-dimensional ultrasound. Li et al (26) also reported that the BRAFV600E mutation was not associated with the features of 2-dimensional ultrasound (including tumor size, tumor border, or calcification). In the present study, a statistical significant difference was identified between five features of conventional and contrast-enhanced ultrasound, namely, microcalcification, aspect ratio, nodule size following enhancement, enhancement mode and enhancement time, and the BRAFV600E gene mutation status, using univariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Luo et al (25) reported that the BRAFV600E mutation was associated with the features of the nodules on elastography, but not with the features on 2-dimensional ultrasound. Li et al (26) also reported that the BRAFV600E mutation was not associated with the features of 2-dimensional ultrasound (including tumor size, tumor border, or calcification). In the present study, a statistical significant difference was identified between five features of conventional and contrast-enhanced ultrasound, namely, microcalcification, aspect ratio, nodule size following enhancement, enhancement mode and enhancement time, and the BRAFV600E gene mutation status, using univariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Our results were consistent with their findings, with microcalcification, hypoechogenicity, lobulated margins, and an aspect ratio of greater than 1 being independent risk factors for BRAF mutations. However, it was also shown that BRAF V600E mutations were not associated with tumor size, tumor border, or calcification ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlations between the presence of BRAF V600E mutations and sonographic findings in PTC are widely described, although there are also a few reports in which such associations were not observed [29,38]. The authors of these reports analyzed the US patterns of BRAF V600E -positive and –negative tumors without any assessment of the PTC variants.…”
Section: Genetic Drivers and Sonographic Pattern Of Different Varimentioning
confidence: 99%